Relatório do desenvolvimento humano 2020 - United Nations Development Programme (United Nations, 2021)
The 30th Anniversary 2020 Human Development Report is the latest in the series of global Human Development Reports published by the United Nations Development Programme (UNDP) since 1990 as independent and analytically and empirically grounded discussions of major development issues, trends and policies. This report offers a thought-provoking, necessary alternative to paralysis in the face of alarming planetary change. Its release comes as the COVID-19 (coronarvirus) pandemic simultaneously offers a glimpse of what a ‘new normal’ could hold and opens up the opportunity for humanity to change course. The report also sets out new metrics of human development to guide us, including a new, experimental Planetary pressures-adjusted Human Development Index.